Effect of Ablution on the Incidence of Insomnia in the Elderly - M. Farid Hamzens; Raghib Filhaq; Aragar Putri; Nazarwin Saputra; Muklasin Muklasin (Indonesian Journal of Islam and Public Health, 2021)
Elderly people are very susceptible to insomnia, and if left untreated will cause problems such as excessive daytime drowsiness, attention and memory problems, depressed mood, frequent falls, improper use of hypnotics, emotions become unstable, body and face less fresh and decreased quality of life. So that the right handling is needed to overcome it with one way to use ablution therapy. This study aimed to determine the influence of ablution with insomnia on the elderly. This article is a type of literature review article reviewing journals about the effect of ablution on the incidence of insomnia in the elderly downloaded via the journal portal. Based on the results of research conducted by researchers, it can be concluded that the influence or relationship of ablution with the incidence of insomnia in the elderly, this is because ablution can reduce muscle tension and become more relaxed, so that the elderly can have good quality sleep. There is the effect of ablution with the incidence of insomnia in the elderly. It is recommended to continue interventions for ablution before going to bed independently and supervised by nurses if they are in the institution for a long period of time to improve the health of the elderly and prevent stress, depression and other illnesses.